Case report: An intriguing case of Philadelphia chromosome–positive acute lymphoblastic leukemia recurrence - Peccatori, Nicolò; Chiocca, Elena; Conter, Valentino; Tondo, Annalisa; Marzorati, Matilde; Casini, Tommaso; Veltroni, Marinella; Biondi, Andrea; Fazio, Grazia (Frontiers in Oncology, 2024)
The incorporation of tyrosine kinase inhibitors (TKIs) in the treatment of Philadelphia chromosome–positive acute lymphoblastic leukemia (Ph+ ALL) led to significant improvement. However, in the pediatric setting, the outcomes of Ph+ ALL are still inferior compared to those of other ALL subtypes even in the TKI era due to higher relapse rate. Herein, we report a very peculiar case of late extramedullary Ph+ ALL relapse in a child, characterized by lymphomatous presentation in the tonsils and lymphoid lineage switch. The diagnostic dilemma between the occurrence of a second malignant neoplasm and the recurrence of the primary disease is further discussed, highlighting the importance of molecular backtracking analysis. This case report emphasizes the high plasticity and polyclonal nature of ALL and expands the heterogeneity of possible clinical presentation of Ph+ ALL at relapse.